Carrier frequency of the recurrent mutation c.1643_1644delTG in the XPC gene and birth prevalence of the xeroderma pigmentosum in Morocco - DOUBAJ, Yassamine; LAARABI, Fatima-Zahra; CHAFAI ELALAOUI, Siham; BARKAT, Amina; SEFIANI, Abdelaziz (Journal of dermatology, 2012)
Xeroderma pigmentosum (XP) is an autosomal recessive inherited disease which is genetically heterogeneous. The prevalence of this genodermatosis is estimated to be 1/1 000 000 in the USA; it is more common in Japan and probably in other populations with high levels of consanguinity. The molecular diagnosis and identification of mutation in patients requires the knowledge of the causative gene by the determination of XP complementation groups. Soufir et al. have reported that XPC is the major disease‐causing gene with a recurrent mutation in the Mediterranean region. The mutation c.1643_1644delTG (p.Val548AlafsX25) represents alone 74% of all the XP probands tested and 87% in XP type C in North African patients with founder effect. We used molecular epidemiological methods in the present study to calculate the frequency of heterozygote for this mutation in Moroccan newborns and estimate the prevalence of XP in the Moroccan population. DNA extracted from umbilical cord blood samples of 250 newborns were tested for the recurrent XPC mutation c.1643_1644delTG using real‐time polymerase chain reaction. Heterozygotes profiles were confirmed by direct sequencing. Among 250 newborns tested, one subject was heterozygous for the mutation c.1643_1644delTG. The carrier frequency was estimated to be 1/250 which would imply that the prevalence of XP would be approximately 1/80 504 considering the effect of consanguinity. This is the first report of the prevalence of XP in an Arab country and it shows that the prevalence of xeroderma pigmentosum is higher than that found in Europe and the USA.